2015
DOI: 10.1016/j.jand.2014.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Partial Meal Replacement Plan and Quality of the Diet at 1 Year: Action for Health in Diabetes (Look AHEAD) Trial

Abstract: Background Little is known about diet quality with a reduced-energy, low-fat, partial meal replacement (PMR) plan, especially in individuals with type 2 diabetes. The Action for Health in Diabetes (Look AHEAD) trial implemented a PMR plan in the intensive lifestyle intervention (ILI). Objective Compare dietary intake and percent meeting fat-related and food group dietary recommendations in ILI and diabetes support and education (DSE) groups at 12 months. Design Randomized controlled trial, comparing ILI to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 23 publications
3
19
1
Order By: Relevance
“…High‐carbohydrate diets (>45% total energy intake from carbohydrate or >225g carbohydrate per day) typically represent ‘healthy’ or ‘prudent’ eating patterns and are recommended for the general population. One challenge of using either %total energy intake or absolute amount of carbohydrate was demonstrated in the Look AHEAD trial, in which the dietary intervention provided 50.8% total energy intake from carbohydrate , although, as total energy intake was restricted to induce weight loss, the absolute amount of carbohydrate met the definition of a moderate carbohydrate diet.…”
Section: Resultsmentioning
confidence: 45%
See 1 more Smart Citation
“…High‐carbohydrate diets (>45% total energy intake from carbohydrate or >225g carbohydrate per day) typically represent ‘healthy’ or ‘prudent’ eating patterns and are recommended for the general population. One challenge of using either %total energy intake or absolute amount of carbohydrate was demonstrated in the Look AHEAD trial, in which the dietary intervention provided 50.8% total energy intake from carbohydrate , although, as total energy intake was restricted to induce weight loss, the absolute amount of carbohydrate met the definition of a moderate carbohydrate diet.…”
Section: Resultsmentioning
confidence: 45%
“…High-carbohydrate diets (>45% total energy intake from carbohydrate or >225g carbohydrate per day) typically represent 'healthy' or 'prudent' eating patterns and are recommended for the general population. One challenge of using either %total energy intake or absolute amount of carbohydrate was demonstrated in the Look AHEAD trial, in which the dietary intervention provided 50.8% total energy intake from carbohydrate [27], although, as total energy intake was restricted to induce weight loss, the absolute amount of carbohydrate met the definition of a moderate carbohydrate diet. Nine recent systematic reviews and meta-analyses of the effects of carbohydrate restriction on HbA 1c considered in the present review consistently reported a short-term improvement, maintained over 6-12 months, but which was not maintained over the longer term [16][17][18][19][20][21][22][23][24].…”
Section: Glycaemic Controlmentioning
confidence: 99%
“…Use of meal replacement plans prescribed by trained practitioners, with close patient monitoring, can be beneficial. Within the intensive lifestyle intervention group of the Look AHEAD trial, for example, use of a partial meal replacement plan was associated with improvements in diet quality (34). The diet choice should be based on the patient's health status and preferences.…”
Section: Lifestyle Interventionsmentioning
confidence: 99%
“…Use of meal replacement plans prescribed by trained practitioners, with close patient monitoring, can be beneficial. Within the intensive lifestyle intervention group of the Look AHEAD trial, for example, use of a partial meal replacement plan was associated with improvements in diet quality (23). The diet choice should be based on the patient's health status and preferences.…”
Section: Lifestyle Interventionsmentioning
confidence: 99%